The relationship of users’ acceptance factors and the acceptance of Electronic Documents Management System (EDMS) implementation: a case study at Universiti Malaysia Sarawak (UNIMAS)/ Thymie Pengabang Mangik - Mangik, Thymie Pengabang (2017)
This research was conducted to investigate the relationship between the users’ acceptance factors and the acceptance of EDMS implementation, at Universiti Malaysia, Sarawak (UNIMAS). Data were collected from five different departments at UNIMAS. This data used to study the relationships among two parameters: (a) the independent variables called as Perceived Usefulness and Perceived Ease of Use; and users; acceptance of EDMS implementation. A correlation analysis was conducted, controlling for perceived usefulness and perceived ease of use data. The total population for the study was 107 and the sample size was 80 but researcher have analysed up to 100 in order to ensure enough participants for data analysis technique Components of perceived usefulness and perceived ease of use had statistically significant relationships with users’ acceptance of EDMS implementation.In concerning the correlation between perceived usefulness and user acceptance of EDMS implementation, it was positive, medium and significant (r=.336, n=100, p<0.01). In concerning the correlation between perceived ease of use and user acceptance of EDMS implementation, it was positive, small and significant (r=.268, n=100, p<0.01). The higher the perceived usefulness and perceived ease of use towards the system, higher the level of users’ acceptance of EDMS. The results of the study showed that both perceived usefulness and perceived ease of use showed a positive correlation towards the acceptance of EDMS implementation and exhibit significant direct effect on the dependent variables. The study also found that there was an increasing interest of technology acceptance as major determinants of any IT adoption. Finally, the study also suffered from several limitations such as methodological limitation and researcher limitations.